Field evaluation of spent pleurotus ostreatus substrate reveals limited suppression of fusarium wilt in banana - Ocimati, Walter; Ogwal, Geofrey; Kearsley, Elizabeth; Blomme, Guy (MDPI, 2025)
Fusarium oxysporum f. sp. cubense (Foc), the causal agent of Fusarium wilt of banana, can persist in the soil for extended periods as chlamydospores or endophytes in weeds, complicating control measures. No single control strategy is effective. Biological agents present an increasingly important control option. This study explored the potential of the spent P. ostreatus substrates (SPoS) to suppress Foc R1 in a field with high Foc inoculum, following laboratory and greenhouse studies that highlighted the potential of P. ostreatus as a biocontrol agent against Foc. A susceptible cultivar ‘Sukali Ndizi’ and a resistant cultivar ‘Mpologoma’ were used for the study. SPoS was compared with farmyard manure (FYM), a combination of SPoS with FYM and a control without treatment. A one-time application of the treatments at planting did not consistently and significantly (p > 0.05) reduce the prevalence and severity of leaf symptoms, pseudostem splitting and corm damage in the mother and ratoon plants of the susceptible cultivar. No symptoms occurred in ‘Mpologoma’. SPoS applications at planting and after every two months over an8-month period did not significantly reduce leaf symptoms and corm damage in ‘SukaliNdizi’, while it increased pseudostem splitting. The marginal and irregular reductions in FW could be due to an observed high weevil damage in SPoS treatments and other confounding factors such as weather, SPoS quality, and pathogen load in the field. Further research on weevil SPoS interactions, use of P. ostreatus mycelium-rich substrate, and other confounding factors is crucial for fine tuning P. ostreatus use.